Oral health and oral health behavior in young adults with caries disease - Jennie Hagman; Ulla Wide; Helene Werner; Magnus Hakeberg (Nature Publishing Group, 2021)
Abstract Objective The aim of this study was to describe and analyze oral health, oral health behaviors, and oral health-related quality of life (OHRQoL) in relation to the level of caries disease among caries-active young adults. Material and methods This study presents data from a sample of young adults (n = 135) with active caries disease who were enrolled in a clinical, randomized controlled trial. The independent variables of sociodemographics, oral health (gingivitis, plaque), oral health behaviors (such as toothbrushing, dental attendance, sugar-containing sweets and drinks), dental anxiety, self-rated oral health, and OHRQoL were collected. Multinomial logistic regression was used to simultaneously evaluate the associations between the independent variables and caries severity. Results Multinominal logistic regression showed that poor OHRQoL and gingivitis were associated with caries severity in a gradient fashion in accordance with caries disease activity. Also, irregular dental care and frequent consumption of sugary soda were significantly associated with very high caries severity. Conclusions The risk factors related to caries severity among young adults were poor OHRQoL, gingivitis, consumption of sugary soda and irregular dental care attendance, indicating the need for a combination of different interventions specifically health behavior change. Furthermore, these findings may contribute to identifying high caries-risk individuals.